2014
DOI: 10.1177/1535370214539227
|View full text |Cite
|
Sign up to set email alerts
|

HPLC analysis and extraction method of SN-38 in brain tumor model after injected by polymeric drug delivery system

Abstract: SN-38 is a highly potent anticancer drug but its poor solubility in aqueous solvent and adverse side effects limit clinical applications. To overcome these limitations, SN-38-loaded-injectable drug delivery depots have been intratumorally administered in xenograft tumor model in nude mice. The extraction and high performance liquid chromatography (HPLC) were performed in order to determine the amount of SN-38 inside tumors. SN-38 was extracted from tumors using DMSO. HPLC analysis was validated and resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Recent reports demonstrated that SN-38-loaded polymeric micelles or depots enhance and prolong the distribution of free SN-38 in vivo [35,38,39], and exert a potent antitumor effect against MG cells in vitro [38,40] and in animal models [19,35,41]. The effective release of SN-38 was reported to range from 14 h to 18 days [19,38,40,41]. In the present study, SN-38 was successfully loaded into PLGA microparticles [42] by using the electrospraying technique.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recent reports demonstrated that SN-38-loaded polymeric micelles or depots enhance and prolong the distribution of free SN-38 in vivo [35,38,39], and exert a potent antitumor effect against MG cells in vitro [38,40] and in animal models [19,35,41]. The effective release of SN-38 was reported to range from 14 h to 18 days [19,38,40,41]. In the present study, SN-38 was successfully loaded into PLGA microparticles [42] by using the electrospraying technique.…”
Section: Discussionmentioning
confidence: 64%
“…In an MG-bearing athymic/nude mice study, intratumoral administration of CPT-11 or SN-38 extended the average survival time of the MG-bearing animals from 22 days to 46 and 65 days, respectively [33]. Recent reports demonstrated that SN-38-loaded polymeric micelles or depots enhance and prolong the distribution of free SN-38 in vivo [35,38,39], and exert a potent antitumor effect against MG cells in vitro [38,40] and in animal models [19,35,41]. The effective release of SN-38 was reported to range from 14 h to 18 days [19,38,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, serum was added with cold methanol then the mixture was centrifuged at 14,000 rpm, 10°C for 10 min. The supernatant was filtered and determined for drug concentration by HPLC [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 18,19 ] Nittayacharn et al . [ 20 ] validated HPLC method for the determination of SN‐38 inside tumours. The linear range was 0.03–150 μg·ml −1 , with lower limit of detection of 0.308 μg·ml −1 and lower limit of quantitation of 1.02 μg·ml −1 .…”
Section: Introductionmentioning
confidence: 99%